Breast self-examination as a route to early detection in a lower-middle-income country: assessing psychosocial determinants among women in Surabaya, Indonesia - Triana Kesuma Dewi; Robert A. C. Ruiter; Merle Diering; Rahkman Ardi; Karlijn Massar (BMC, 2022)
Abstract Background Breast cancer has become a public health concern in Indonesia. Regular breast self-examination (BSE) is considered an important first step for its early detection, especially in countries with limited healthcare access, as it is the case in Indonesia. This study aimed to confirm and assess the psychosocial determinants of intention to perform BSE and BSE performance. Methods The cross-sectional study was conducted on 204 women aged 18-65 years in Surabaya, Indonesia. A 64-item survey was conducted, included variables from the Reasoned Action Approach, and the Health Belief Model, presented questions about demographics, breast cancer knowledge, and behavior related to BSE. Results Most women (72.5%) expressed intention to perform BSE; however, only 7.8% and 2.9% performed BSE per week and per month, respectively, in the past year. Breast cancer knowledge and attitudes towards BSE were uniquely associated with BSE performance. Perceived behavioral control (PBC) and BSE attitudes were unique correlates of intention. Perceived benefits and barriers and subjective norms were significantly associated with intention and BSE behavior in bivariate analyses. Conclusions Breast screening education should incorporate strategies for improving attitudes towards BSE, PBC, and breast cancer knowledge with perceived benefits and barriers and subjective norms as relevant targets.